«PHILOSOPHY» AS AN EDUCATIONAL COURSE: THE CHANGE OF THE CONCEPT - V. M. Karelin; N. I. Kuznetsova; I. N. Griftsova (Высшее образование в России, 2017)
The article addresses the problem of the change of conceptual grounds of teaching the educational course of philosophy. The thematic waymarks we offer have been developed as a part of the Government Contract Project for the layout of the according conception of the course and the indicative working program of the discipline for undergraduate students of non-philosophical humanitarian specialties.